MEDICAL AND PEDAGOGICAL ASPECTS OF DESIGNING OF INDIVIDUAL PROGRAM OF DEVELOPMENT OF CHILDREN WITH HEAVY AND MULTIPLE DISORDERS - Ольга Юрьевна Синевич; Татьяна Юрьевна Четверикова (The Publishing House Medicine and Enlightenment, 2017)
The article presents recommendations for compiling an individual development program for schoolchildren with severe and multiple disabilities. The main content of the program parts is reflected. The need for a comprehensive survey of children with health problems at the program preparation stage is underlined. An example of a child's characteristics is given, which is compiled according to the results of the diagnosis. The role of medical and pedagogical workers in the implementation of an individual developmental route for children with severe and multiple disabilities is disclosed.